Inovasi Infrastruktur Jalan melalui Pemasangan Reflektor untuk Mencegah Kecelakaan di Desa Pejala Kabupaten Penajam Paser Utara - Butet Wulan Trifina; Dzakiyah Nasywa Aqilah Endhar; Muhammad Atha Naufal; Anisa Ramadhani; Tabita Tabita; Shinta Zahira Pamida; Daffa Najwa Aly Pentium; Aulia Diva Wardana; Muhammad Pasha Melandri Yusuf; Nasywa Khairunnisa; Yesha Andi Ana (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
Traffic accidents in rural areas remain a significant problem due to limited road safety infrastructure, particularly low visibility at night, and a lack of safety support devices. Pejala Village in Penajam Paser Utara Regency faces these conditions, characterized by limited public street lighting and the lack of adequate road boundary markers. This community service activity aims to improve visibility and safety for road users through the installation of locally sourced road reflectors. The method used is the Participatory Action Research (PAR) approach by actively involving the community in every stage of the activity. The evaluation was conducted using a simple quantitative approach through measuring visibility, as well as surveying road user perceptions before and after the installation of reflectors, involving 30 respondents. The results of the study showed an increase in road visibility at night, with an average visibility increasing from ±8 meters to ±13 meters or around 60%. In addition, 83% of respondents stated that they felt safer when crossing the road at night. Active community participation in the installation and maintenance process also supports the sustainability of the program. Thus, installing road reflectors made from local materials is an effective, economical, and sustainable solution for improving traffic safety in rural areas.